Reversibility of the effects of natalizumab on peripheral immune cell dynamics in MS patients. (10th October 2017) - Plavina, Tatiana; Muralidharan, Kumar Kandadi; Kuesters, Geoffrey; Mikol, Daniel; Evans, Karleyton; Subramanyam, Meena; Nestorov, Ivan; Chen, Yi; Dong, Qunming; Ho, Pei-Ran; Amarante, Diogo; Adams, Alison; et al.
Abstract : Objective: To characterize the reversibility of natalizumab-mediated changes in pharmacokinetics/pharmacodynamics in patients with multiple sclerosis (MS) following therapy interruption. Methods: Pharmacokinetic/pharmacodynamic data were collected in the Safety and Efficacy of Natalizumab in the Treatment of Multiple Sclerosis (AFFIRM) (every 12 weeks for 116 weeks) and Randomized Treatment Interruption of Natalizumab (RESTORE) (every 4 weeks for 28 weeks) studies. Serum natalizumab and soluble vascular cell adhesion molecule–1 (sVCAM-1) were measured using immunoassays. Lymphocyte subsets, α4-integrin expression/saturation, and vascular cell adhesion molecule–1 (VCAM-1) binding were assessed using flow cytometry. Results: Blood lymphocyte counts (cells/L) in natalizumab-treated patients increased from 2.1 × 10 9 to 3.5 × 10 9 . Starting 8 weeks post last natalizumab dose, lymphocyte counts became significantly lower in patients interrupting treatment than in those continuing treatment (3.1 × 10 9 vs 3.5 × 10 9 ; p = 0.031), plateauing at prenatalizumab levels from week 16 onward. All measured cell subpopulation, α4-integrin expression/saturation, and sVCAM changes demonstrated similar reversibility. Lymphocyte counts remained within the normal range. Ex vivo VCAM-1 binding to lymphocytes increased until ≈16 weeks after the last natalizumab dose, then plateaued, suggesting reversibility of immune cell functionality. The temporal appearance of gadolinium-enhancing lesions was consistent with pharmacodynamic marker reversal. Conclusions: Natalizumab's effects on peripheral immune cells and pharmacodynamic markers were reversible, with changes starting 8 weeks post last natalizumab dose; levels returned to those observed/expected in untreated patients ≈16 weeks post last dose. This reversibility differentiates natalizumab from MS treatments that require longer reconstitution times. Characterization of the time course of natalizumab's biological effects may help clinicians make treatment sequencing decisions. Classification of evidence: This study provides Class III evidence that the pharmacodynamic markers of natalizumab are reversed ≈16 weeks after stopping natalizumab.